Importance of occupation in the increase of gender differences in the advance of telework in Spain - Pilar Ortiz García; Salvador Manzanera-Román (PLoS ONE, 2025)
The COVID-19 pandemic significantly altered forms of labor. In this analysis, which focuses on the Spanish labor market, we consider telework from a gender-based perspective in order to identify whether there is a gender gap in this work form and, if so, whether this is impacted by occupation. The methodology is quantitative in nature, and we apply logistic regression based on data from Eurofound’s European Working Conditions Survey. We investigate how factors including labor characteristics, education, and life stage and cohabitation affect the propensity to engage in telework. The findings reveal the dominance of women in telework, moderated by labor characteristics (occupation, type of contract, and working day) and educational variables.